COMPARISON OF INFORMATION AND EFFICIENCY OF RADIATION METHODS OF EXAMINATION IN CHILDREN WITH RETENTIAL TEETH - Ткаченко П. І.,; Dmitrenko, M.I.; Cholovskyi, M.O. (World of Medicine and Biology, 2019)
Not paying attention to the rapid development and introduction into medical practice of the latest medical diagnostic technologies, such as: computer and magnetic resonance imaging, X-ray research method, as a rule, remains an integral part of the diagnostic stages in dentistry [4]. 46 children aged 8 to 14 years old with retented and dystrophized teeth were examined in which, in a certain sequence, according to the indications, 46 intraoral radiograms, 17 orthopantomograms and 9 KT results were evaluated. X-ray examination for dystopia and retention of teeth in the frontal area of the upper jaw was carried out with the aiming of an X-ray image in 46 children to determine their location in the bone tissue and assess the degree of their retention. [9]. In 17 patients (37%) this kind of radiological diagnosis did not satisfy its informative nature, therefore they were additionally conducted orthopantomogram. Under these conditions, the atypical arrangement of the incisors on the upper jaw was visualized and the general state of the tooth-jaw system was more accurately determined. In 8 cases (47%), out of 17, there was a difficulty with interpretation regarding the location of the located teeth. For a more detailed examination, they subsequently performed X-ray diagnostics with the help of a CBCT device. On the sections, the precise position, the size of the retinal teeth, the shape and depth of their occurrence in the bone tissue were determined. After comparing the characteristics of radiation diagnostic methods in pediatric surgical dentistry and orthodontics, we came to the conclusion that the most informative and more accurate method is a cone-ray computer tomography in various difficulty conditions.
Keywords: dystopia; retention; X-ray; diagnostics; orthopantomogram; dental cone beam computer tomography